2022
DOI: 10.1155/2022/9735626
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Defensins to Counter COVID-19 as Furin Inhibitors: In Silico Efficiency Prediction and Novel Compound Design

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was characterized as a pandemic by the World Health Organization (WHO) in Dec. 2019. SARS-CoV-2 binds to the cell membrane through spike proteins on its surface and infects the cell. Furin, a host-cell enzyme, possesses a binding site for the spike protein. Thus, molecules that block furin could potentially be a therapeutic solution. Defensins are antimicrobial peptides that can hypothetically inhibit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, the probable consequences of numerous other mutations have stayed obscure. In general, genetic investigations are labor-intensive, time-consuming, and costly, while bioinformatic studies offer superior intuition into the right pathway of empirical research and considerably diminish expense and time [ 53 ]. Therefore, the present research tried to recognize functionally imperative nsSNPs in ADAM33 proteins using a variety of bioinformatic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the probable consequences of numerous other mutations have stayed obscure. In general, genetic investigations are labor-intensive, time-consuming, and costly, while bioinformatic studies offer superior intuition into the right pathway of empirical research and considerably diminish expense and time [ 53 ]. Therefore, the present research tried to recognize functionally imperative nsSNPs in ADAM33 proteins using a variety of bioinformatic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and co-workers reported that HD-5 can inhibit spike-protein-expressing pseudovirions from binding ACE-2 on enterocytes, ultimately preventing CoV-2 infection [166]. In silico docking studies predicted that LL-37, theta-defensins and HBD-2 can bind the RBD of SARS-CoV-2 [167][168][169]. Biochemical analyses further validated that HBD-2 indeed has strong affinity towards RBD, which prevented the fusion of S-protein expressing pseudovirions with ACE-2 on human cells [169].…”
Section: Application Of Hdps For the Management Of Covid-19mentioning
confidence: 99%
“…Nowadays, bioinformatics tools can be used to analyze the properties of different compounds and even their biological effects with computational mathematical studies with less time and lower cost than laboratory studies and clinical trials (Negahdaripour et al 2022 ). Bioinformatics also provides accurate insight for discovering and designing creative therapeutic compounds.…”
Section: Bioinformatics Study and Computational Analysis Of Probiotic...mentioning
confidence: 99%
“…There are no approved management protocols, and treatment regimens among all the drug treatments suggested to date for SARS-CoV-2 (Cunningham et al 2020 ). Numerous clinical trials were conducted to evaluate a variety of medicines such as hydroxychloroquine, lopinavir/ritonavir, corticosteroids, and remdesivir for this disease, and the clinical protocols are being updated continually (Negahdaripour et al 2022 ). The effectiveness of most of these medicines is under question for the management of SARS-CoV-2; therefore, the clinical prognosis may be unpredictable according to the lack of clinical evidence.…”
Section: Introductionmentioning
confidence: 99%